Muslim Bank as a Historical Category: Creating Credit Institutions for Muslims In the First Half of the 20 th Century - R. I. Bekkin (Vestnik MGIMO-Universiteta)
Abstract: The article examines theoretical and practical aspects of the activities of Muslim banks in the countries of Eurasia in the first half of the 20th century. These credit institutions were created on the initiative of Muslim entrepreneurs who sought to have an affordable source of financing for their activities. Muslim banks were an important element of the financial system of a number of countries during the era of colonialism. In the context of competition in the capital markets between Western banks and credit institutions belonging to different religious and ethnic groups, as well as competition of the latter with each other, Muslim banks acted as an instrument for ensuring the economic independence of Muslim communities in a number of countries and regions in the period under review. After the countries of Asia gained independence, Muslim banks were transformed into ordinary national banks.The activities of Muslim banks are considered in the article against the background of discussions on the admissibility of loan-based banking operations in the context of the prohibition of usury (riba) in Islamic law. The article emphasizes that Muslim banks in their activities relied on the theological and legal conclusions (fatwas) of Islamic scholars who considered such activities legitimate and not falling under the Quranic concept of usury.The author adheres to the point of view that the creation of an independent state or nationalterritorial / national-cultural autonomy of Muslims was a natural result of the struggle of the Muslim bourgeoisie with competitors for the markets for goods and services in a number of countries and regions, considering both Muslim and Islamic banks only as a certain stage in the development of banking in a number of countries in Asia, Africa and Europe.The article disputes the idea that both Islamic banks and the Islamic economic model as a whole are monolithic structures that cannot be modified. According to the author, the very creation of Islamic banks, as well as their convergence with conventional (non-Islamic) credit institutions, which we observe today, is a natural result of a change in the economic interests of the ruling class both in the countries of the spread of Islam and in the Western world.The article examines the history of the creation of Muslim banks in Bosnia and Herzegovina and in British India. These regions are brought together by the fact that Muslims who lived there were forced to compete with representatives of other ethno-confessional groups and communities living in the same territory. Particular attention is paid to the theological and legal discussions on the creation of a Muslim bank in Russia.